What Kind of Teachers Guide the Future Primary School Teacher's Internship? - Ernesto Colomo; Vicente Gabarda (Universidad Autónoma de Madrid, 2019)
During the internship, the school's tutors become examples for the professional development of the students. In this sense, the purpose of this research is to identify the archetypes of teachers who guide to the future primary teachers, based on the proposal of Esteban y Mellen (2016). The sample is composed by 230 students enrolled in any of the four internship subjects of the Primary Education Degree, in the 2017-2018 course. Based on a qualitative descriptive-interpretative perspective, the characteristics of the tutors in the workplaces have been analysed, through the content analysis of the students' reports. The results show that the most frequent archetype is the personal and authentic teacher, highlighting a caring attitude towards the professional and personal relationships with the students. Aspects like the content domain of the teacher transmitter of stories or the educational innovation of the teacher motivator of learning have also been collected. The conclusions suggest the importance of the way of being and exercising the educational processes from the tutors due to their influence in the students' teacher professional identity construction.